Cation transport abnormalities in vivo in untreated essential hypertension. - Boon, N; Aronson, J; Hallis, K; Grahame-Smith, D (1986)
In order to study cation transport in vivo we have measured the changes in plasma and intra-erythrocytic rubidium concentrations after the oral administration of rubidium chloride. In this paper we describe our findings in 22 patients with untreated essential hypertension, compared with the findings in 22 carefully matched control subjects. Our findings in patients receiving short-term digoxin therapy and in patients with chronic renal failure are also included for comparison. Whereas the findings in patients receiving digoxin and in patients with chronic renal failure are compatible with a widespread reduction in sodium, potassium-ATPase activity in vivo, the findings in patients with untreated essential hypertension are not. Further analysis of the data and a similar study of the disposition of 42K after the intravenous administration of 42KCl suggest that in vivo net cation transport is enhanced in the erythrocytes of patients with untreated essential hypertension.